Love Affair in the Garden of Milton : Loss, Poetry, and the Meaning of Unbelief - Mintz, Susannah B., 1965- (Book collections on Project MUSE., 2021)
"Love Affair in the Garden of Milton interweaves the private story of a marriage coming apart with readings of John Milton's poetry and prose. Connected essays explore the chaos of loss and the discovery of how a writer can inhabit our emotional as well as our intellectual selves. Inflected by the principles of mindfulness, Susannah B. Mintz's work of expressive life writing explores how we reconstruct ourselves and find our way back to meaning in the aftermath of trauma. Her memoir reflects on a series of affairs, beginning with the author's discovery of her husband's infidelity and their immediate separation because of it, events that offer a starting point but ultimately prove less significant than her resulting search for what still matters in a world rocked beyond recognition. Navigating mourning and the reeling, disorienting pain of betrayal, Mintz's essays animate her surprise, as well that of her students, that Milton and his world-bending heresies can be not just critically relevant but emotionally reassuring, especially in the context of grief. Buddhist teachings and meditation practices align with Milton in ways that further help Mintz grapple with the upheaval of heartbreak, explore the meaning of "meaning," and find a way toward equanimity and calm. Formally inventive and engaging complex philosophical ideas, Love Affair in the Garden of Milton raises questions of forgiveness, desire, identity, grief, and the counterintuitive relevance of literary tradition. This lyric memoir offers readers a sense of partnership, with the author and Milton as companionable guides through the wilds of love and loss"--